THE INFLUENCE OF ENTREPRENEURIAL ORIENTATION ON SME'S PERFORMANCE THROUGH ENTREPRENEURIAL COMPETENCY IN PASAR JAMBI - Riante, Christine; Utama, Louis (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to determine the effect of entrepreneurial orientation on business performance through the entrepreneurial competence of Culinary SMEs in Pasar Jambi. Micro, Small, and Medium Enterprises (SMEs) play an important role in economic development. So entrepreneurs need to develop entrepreneurial orientation and entrepreneurial competencies to maintain their business performance in this uncertain pandemic period. The researcher distributed questionnaires to 59 samples of SMEs in Pasar Jambi using the purposive sampling technique, then processed using SmartPLS-SEM to analyze data and test hypotheses. The study results show a positive relationship among entrepreneurial orientation and entrepreneurial performance, entrepreneurial orientation and entrepreneurial competence, entrepreneurial competence, and entrepreneurial performance. In addition, entrepreneurial competence is mediating entrepreneurial orientation and entrepreneurial performance.